Control of period doubling bifurcation in an SMIB power system using adaptive controller based on LaSalle's invariant principle. Issue 1 (1st January 2017) - Rout, Bimalesh Chandra; Lal, Deepak Kumar; Barisal, A.K.
Abstract: This paper presents when system parameter falling into certain area, the single machine infinite bus system with excitation limits experience period doubling bifurcation. When the parameters are further changed the system shows chaotic oscillations. To control this, an adaptive controller based on LaSalle's invariant principle is designed. The control method does not need any analytical knowledge about the system dynamics and operates without any proper information of the preferred steady state position. Numerical simulation results show the effectiveness of the controller and also it help to maintain the stable operation of the power system.